Implementation of Government Accounting Standards, the Role of Internal Audit and Apparatus Competence on the Quality of Accounting Information at the Regional Drinking Water Company (PDAM) Tirta Bening Pati District - Marhamah, Marhamah; indriastuti, ariyani (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
The quality of accounting information is very important for effective decision making by various stakeholders. To achieve good quality information, it must ensure compliance with accounting standards, have a strong internal control system, and ensure the competence of its apparatus. The aim of this research is to analyze the influence of government accounting standards, the role of internal audit, and apparatus competency on the quality of accounting information. The research sample was 45 employees of PDAM Tirta Bening, Pati district. The data collection method is by distributing questionnaires to respondents. Data analysis uses multiple linear regression. Based on the results of the data instrument test, valid and reliable results were obtained. This research also meets the classic assumption test criteria. The research results show that government accounting standards, the role of internal audit, and apparatus competency have a significant effect on the quality of accounting information. Key words: Implementation of government accounting standards, Role of internal audit, Apparatus competence, Quality of accounting information